The effect of the Ant25, Ant26 and Ant27 loci controlling proanthocyanidin synthesis in barley (Hordeum vulgare L.) grain on plant growth and development - I. V. Totsky; R. Li; O. Yu. Shoeva (Труды по прикладной ботанике, генетике и селекции, 2024)
Background. Barley grain contains such flavonoid compounds as proanthocyanidins. Despite their positive effect on plant adaptation to environmental conditions, they can worsen the quality of raw materials used in barley products. In this context, releasing proanthocyanidin-free cultivars is an important task. Mutants at the Ant25, Ant26 and Ant27 loci with unknown molecular functions can be used as donors of recessive alleles of the genes specifically controlling proanthocyanidin synthesis in barley grain. This study explored the effect of these loci on barley plant growth and development. A conclusion was made about their functional role in the biosynthesis of flavonoids and the expediency of using such mutants in the breeding of proanthocyanidin-free cultivars.   Materials and methods. The weight of grains, roots and shoots, the length of the main shoot, and the number of lateral shoots were measured in mutants and original cultivars grown in a hydroponic greenhouse. The harvest index was calculated as the ratio of grain weight to total plant biomass. Differences between genotypes were assessed using the Mann–Whitney U-test.   Results. The ant25.264 and ant27.488 mutants showed lower values of all analyzed characters than the parental cultivars ‘Secobra18193’ and ‘Zenit’, respectively. The ant27.2043 mutant had a shorter main shoot, less grain weight, and lower harvest index compared to cv. ‘Arena’, but did not differ from the original cultivar in other characters. Mutants at the Ant26 locus demonstrated no differences from the parental cultivar ‘Grit’ in all parameters, except the ant26.486 mutant whose root weight exceeded the cultivar’s value.   Conclusion. The effect of the Ant25 and Ant27 loci on plant growth and development was proved. Mutants at the Ant26 locus, with no negative effect on plant development, may be recommended to barley breeders as promising donors for the development of proanthocyadin-free cultivars.